Post break-up experiences of Filipino male and female adolescents from a selected university in Metro Manila - Dela Paz, Joseph Willie De Leon; Juliano, Andrea Faye.; Juadiong, Lillian Leynes (Quezon City UP College of Home Economics, 2012)
The present study sought to gain a deeper understanding and a greater appreciation of Filipino male and female adolescent students' post break-up experiences. It explored the relationship of gender and experiences of college students in romantic relationship dissolutions. It also determined the lessons that these adolescents learned from the whole experience. 30 male and 30 female students from the different colleges in the University of the Philippines-Diliman were purposively selected to participate in this study. The respondents of the study were asked to accomplish a questionnaire containing demographic questions about themselves and the context of their relationships. Afterwards, interviews were done to better probe on the experiences and lessons that they learned from the romantic relationship break-up. Data gathered from these methods were grouped into themes using thematic tables and were ranked according to their frequency. A chi-square test was also done to check for significance between the male and female responses. Researches found that there are various challenges and difficulties that an adolescent goes through after break-up. There are also numerous activities, changes in one's self and people that adolescents talked to in order to move-on from a romantic relationship break-up. Results also show that, during post break-up experiences, there is no significant difference between males and females as to how they undergo their respective romantic relationship break-ups. Similarly, the study yielded no significant difference between perceived lessons learned of males and females. These post break-up experiences were further discussed using Kubler-Ross' Five Stage of Grief and Carol Giligan's Perspective on Gender Differences. It suggested that future researches expand the scope of study and scrutinize more means of measure for romantic relationships.
Thesis (BSFLCD)--University of the Philippines.
Keywords: Adolescents -- Philippines